Emissions from Wood Stoves and Health Impacts Assessments - a Critical Review - Oyvind Skreiberg (Chemical Engineering Transactions)
As wood stoves are widely used for space heating, they also contribute significantly to health impacts through emissions to air, alongside several other emission sources, e.g. traffic. These emissions have various health impacts, on a short to a very long timescale. It would be very valuable to be able to accurately quantify the contribution of a specific emission source or emission producing technology to specific health impacts to assess corresponding health costs and the effect of technology improvements on the reduction of these costs and the improvement of human health. Several efforts have been done to quantify health impacts of air pollution in general and the contribution from different emissions sectors, as done annually by the European Environment Agency (EEA) for Europe and the individual countries based on mainly data from emission monitoring stations in the different countries and emission factors for the different emission sectors. More specific studies have also been carried out, trying to assess the impact of individual emission sources and technologies, e.g. the specific contribution by emissions from wood stoves to attributable (premature) deaths and years of life lost for a city. Such an assessment includes many assumptions in addition to relying on emission data resulting from limited emission measurements or atmospheric dispersion modelling. Consequently, large uncertainties are connected to the assessment outcome, and these uncertainties are usually not properly communicated. This gives a reader the impression that the results are more trustworthy than they are, which again can result in serious implications. Therefore, a critical review is needed targeting the data quality and assumptions going into the health impacts assessments, focussing on the contribution of emissions from wood stoves.